Ownership Structure and Dividend Choices in The Context of Islamic Banking: A Case Study of Indonesia - Handhayani, Fathimah Tri; Tazqy, Recha; Handayani, Salvia Suci; Nuryanti, Yuni; Ruhana, Nafisah; Setiawan, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research explores the factors influencing dividend policies based on ownership structure in Islamic Commercial Banks in Indonesia during the period of 2012-2022. Methodology: The sample of this research consists of 16 Islamic Commercial Banks operating in Indonesia and uses secondary data which is analyzed using logistic regression. Results: The results of this research indicate that government ownership has a positive effect on dividend policy. On the other hand, institutional ownership does not affect dividend payment decisions in Islamic Commercial Banks in Indonesia. Applications/Originality/Value: The differences in this research are in the research object, research time, and variables used.